Sight and the Byzantine icon - Lymberopoulou, Angeliki (Body and religion, 2018)
This article addresses the sense of sight through case studies drawn from Byzantine art, the art of Orthodox Christianity. Vision is central to Orthodox worship, facilitated by images known as icons. By enabling the visualization of the invisible divine, the importance of icons is paramount in enhancing the faithful's religious experience.